Analisis Mutu Fisik Dan Kimia Biji Kakao Berdasarkan Pola Ketinggian Lokasi Tanam di Kecamatan Bua Kabupaten Luwu - Isnam Junais; Dewi Sartika (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2022)
Cocoa is a smallholder plantation plant that is spread in various parts of Indonesia. demand for cocoa in the domestic and world markets. an opportunity for Indonesia to make cocoa as a plantation commodity whose role is expected to be able to encourage the national economy. In terms of quality, Indonesian cocoa is not inferior to world cocoa, if it is fermented properly. The quality of cocoa beans is a very important element so efforts are needed to maintain and maintain it. The quality of cocoa beans is determined by various factors, including the use of superior seeds, the process of cacao cultivation, the post-harvest handling process as well as climatic, weather and topographic conditions. The purpose of this study was to determine the physical and chemical quality characterization of cocoa based on the pattern of planting height. The results of the study for physical quality parameters showed that there was no significant effect between the observation variables, namely the height of the planting location with physical test parameters including the length and diameter of the cocoa pods and the number of beans per fruit and per 100 grams, but overall the physical quality of cocoa beans for all Observation parameters are included in the grade A quality category based on SNI standards. Based on the parameters of the chemical quality of cocoa beans, it shows that there is no significant effect of the variable location of the tested cocoa plant height on the fat content of cocoa beans, for the observation variables of cocoa bean moisture content and ash content, each has a significant effect where cocoa plants are above 200 mdpl tends to have higher moisture and ash content than cocoa plants planted at a planting height lower than 200 mdpl. However, in general, the chemical quality of cocoa based on fat content, moisture content and ash content at each observation location was classified as good, which still met the best standards based on SNI cocoa quality standards.